Persistent household food insecurity, HIV, and maternal stress in Peri-Urban Ghana - Garcia, Jonathan (BioMed Central, 2013)
BACKGROUND: The mental health of caregivers has been shown to be important for improving HIV prevention and treatment. Household food insecurity affects hundreds of millions of individuals in Sub-Saharan Africa, a region that experiences a disproportionate burden of the HIV pandemic. Both maternal HIV diagnosis and household food insecurity may be linked with maternal stress. This in turn may lead to unhealthy coping behaviors. We examined the independent associations of HIV, persistent household food insecurity and the synergistic effect of both on maternal stress. METHODS: Ghanaian women recruited prenatally from hospitals offering voluntary counseling and testing (VCT) were followed for 12 months after childbirth (N = 232). A locally adapted 7-item version of the US Household Food Security Survey Module was applied at four time points postpartum. We dichotomized participant households as being persistently food insecure (i.e., food insecure at each time point) or not (i.e., food secure at any time point). We dichotomized participant women as not perceiving vs. perceiving stress at 12 months postpartum in reference to the median sample score on the 4-item Cohen’s stress scale. Binary multivariate logistic regression models were used to assess the independent and interactive effects of maternal HIV and persistent household food insecurity on maternal stress. RESULTS: The proportion of HIV-positive women that lived in severe food insecure households increased over time. By contrast, the HIV-negative group living in severely food insecure households experienced a steady decline across time. HIV-infection (AOR = 2.31, 95% CI 1.29-4.12) and persistent household food insecurity (AOR = 3.55, 95% CI 1.13-11.13) were independently associated with maternal stress in a multivariate model. Being both HIV-positive and persistently food insecure strongly and synergistically increased the risk for maternal perceived stress (AOR = 15.35, 95% CI 1.90-124.14). CONCLUSION: In agreement with syndemic theory there is a powerful synergism between maternal HIV diagnosis and household food insecurity on maternal stress. Comprehensive multi-dimensional intervention studies are needed to better understand how to reduce stress among HIV-positive women living in persistently food insecure households and how to reduce the likelihood of food insecurity in HIV-affected households in Sub-Saharan Africa.